The Influence of Entrepreneurial Motivation and Educational Factors on Students’ Entrepreneurial Intention in the Entrepreneurship Program at USK Mediated by Attitude Towards Entrepreneurship - Malik Maulana Rizki; Amri; Hendra Halim; Chairil Anwar; Syahriyal (International Journal of Kita Kreatif, 2026)
This research investigates the effect of entrepreneurial motivation and educational factors on students’ entrepreneurial intention within the USK entrepreneurship programme, with attitude towards entrepreneurship positioned as a mediating variable. A quantitative method was employed, utilizing path analysis through SmartPLS 4.0. The study involved 135 active students enrolled in the programme, selected using purposive sampling. The model assessment covered outer model evaluation, inner model testing, and hypothesis verification through the bootstrapping procedure. The findings reveal that both entrepreneurial motivation and educational factors positively influence entrepreneurial intention. Nevertheless, attitude towards entrepreneurship does not exert a direct effect on entrepreneurial intention, nor does it serve as a mediator between motivation, education, and intention. These results highlight that while motivation and education significantly contribute to fostering entrepreneurial intention, the role of entrepreneurial attitude is not always a determining psychological element in this context.